A cross-sectional, observational study of the clinico-epidemiological profile of female pattern hair loss in Western India and its association with metabolic syndrome - Shreya Singh; Meena B Makhecha (Wolters Kluwer Medknow Publications, 2023)
Background: The increasing prevalence of female pattern hair loss (FPHL) is an alarming concern. There are many studies on FPHL in the world literature but there is a dearth of Indian data on the same. Aims and objectives: The present study aims to ascertain the demographic variables and clinical features of FPHL in Western India and its association with metabolic syndrome (MetS) to add over and above the existing data. Materials and Methods: Ninety females who were diagnosed with FPHL were included after approval of the institutional ethics committee. Demographic details, detailed history, and clinical features were noted, following which a few blood investigations for diagnosis of MetS were advised and evaluated. Results: Our study population's age ranged from 17 to 65 years, with the mean age of 34.7 ± 1.3 years. According to the Basic and Specific (BASP) classification, The basic pattern prevalence as found in our study was 46.7% for M type, 35.6% for L type, and 17.7% for C type. The FPHL severity score revealed that 82 (91.1%) had advanced disease at presentation. Prevalence of MetS was found to be 34.4% and had a significant correlation with age of onset in years (p=0.041) and severity score (p=0.013) implying that it leads to an early onset and greater severity of FPHL. Conclusion: FPHL is increasingly common among Indian women, who frequently present with a bitemporal recession of the hairline. Calculation of the female pattern hair loss severity index (FPHL-SI) can help in the categorization of patients and assessment of prognosis. MetS should be actively looked for in patients of FPHL and managed accordingly.